Oral treatment with 10% potassium iodide solution for refractory cutaneous-disseminated sporotrichosis in an immunocompetent adult: Case report - Zhuang, Kaiwen; Dai, Yaling; Zhou, Yike; Ke, Yujing; Ran, Xin; Ran, Yuping (Frontiers in Microbiology, 2022)
Sporotrichosis has multiple clinical manifestations and its cutaneous disseminated form is uncommon and usually related to immunosuppressive conditions. We report a 47-year-old male patient with no other comorbidities, presenting with multiple cutaneous nodules and ulcers on left upper limb and right thigh. Until the diagnosis is confirmed, the patient initially accepted expiric antifungal treatment with itraconazole with unsatisfactory results in local hospital. Then, he was treated with voriconazole with slow improvement of his skin lesions. At one point during voriconazole treatment course, the patient briefly self-discontinued the voriconazole for economic reason, and the lesions recurred and worsened. The patient was finally diagnosed with disseminated cutaneous sporotrichosis based on the isolation and identification of Sporothrix globosa. Susceptibility testing revealed the isolate was resistant to itraconazole, fluconazole, voriconazole, terbinefin and amphotericin. Given the patient's poor financial condition, potassium iodide was administered. after 1-month therapy of potassium iodide, he reported rapid improvement of his skin lesions. He continued potassium iodide treatment for another five months until full resolution of lesions..